2008
DOI: 10.1111/j.1365-2141.2008.07107.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ADAMTS13 activity in clinical remission and the risk of TTP relapse

Abstract: Summary Idiopathic thrombotic thrombocytopenic purpura (TTP) is characterized by frequent recurrences. Effective screening for relapses will enable intervention prior to overt episodes of TTP. The present study used a modified assay to detect ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 motif, 13) activity as low as 0·5%. This analytical improvement permits adequate measurement of ADAMTS13 activity levels in 97% of remission samples used for statistical modelling. ADAMTS13 activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 34 publications
(50 reference statements)
8
136
0
1
Order By: Relevance
“…On this basis, there is general agreement that all patients in the acute phase have to receive the most effective treatment [21], and we suggest that, at least presently, the best option is represented by concomitant PE and high dose corticosteroids. At the opposite, three clinical studies clearly showed that patients with severe ADAMTS13 deficiency during remission have a much higher likelihood of relapse [22][23][24]. Since reports of single patients or small case series suggested that chimeric anti-CD20 monoclonal antibodies or cyclosporine help to restore normal ADAMTS13 activity and prevent recurrences, it may be that administration of these drugs to patients with a persistent defect of ADAMTS13 improves their long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, there is general agreement that all patients in the acute phase have to receive the most effective treatment [21], and we suggest that, at least presently, the best option is represented by concomitant PE and high dose corticosteroids. At the opposite, three clinical studies clearly showed that patients with severe ADAMTS13 deficiency during remission have a much higher likelihood of relapse [22][23][24]. Since reports of single patients or small case series suggested that chimeric anti-CD20 monoclonal antibodies or cyclosporine help to restore normal ADAMTS13 activity and prevent recurrences, it may be that administration of these drugs to patients with a persistent defect of ADAMTS13 improves their long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory auto-antibodies identified during the acute episode may be associated with a worse prognosis. Once patients are in remission, severe protease deficiency or the presence of inhibitors is associated with an increased risk of relapse [94] . Congenital TTP occurs due to mutations in ADAMTS13 [95] .…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%
“…The "idiopathic" acquired form of thrombotic thrombocytopenic purpura (TTP) is considered to be an autoimmune condition caused by formation of inhibitory autoantibodies (usually IgG) against the ADAMTS13 (a disintegrin-like and metalloprotease with thrombospondin type 1 motifs-13) protease (25)(26)(27)(28)(29)(30). ADAMTS13 is the vWf-cleaving metalloprotease that is deficient in activity either by a congenital genetic mutation or an acquired autoimmune condition in TTP (25,28,29).…”
Section: Thrombotic Thrombocytopenic Purpuramentioning
confidence: 99%